2010
DOI: 10.1063/1.3374701
|View full text |Cite
|
Sign up to set email alerts
|

Large-scale statistical analysis of early failures in Cu electromigration, Part I: Dominating mechanisms

Abstract: With continuing scaling of Cu-based metallization, the electromigration ͑EM͒ failure risk has remained one of the most important reliability concerns for advanced process technologies. The main factors requiring attention are the activation energy related to the dominating diffusion mechanism, the current exponent as well as the median lifetimes and lognormal standard deviation values of experimentally acquired failure time distributions. In general, the origin and scaling behavior of these parameters are rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 22 publications
3
7
0
Order By: Relevance
“…the nonfailed links in the EM failure distribution have been included in the data analysis as censored values to enable a direct comparison to the singlelink data. Details of this calculation were reported earlier [9,11]. The lifetime distributions of differently sized test structures line up well.…”
Section: Methodssupporting
confidence: 62%
See 2 more Smart Citations
“…the nonfailed links in the EM failure distribution have been included in the data analysis as censored values to enable a direct comparison to the singlelink data. Details of this calculation were reported earlier [9,11]. The lifetime distributions of differently sized test structures line up well.…”
Section: Methodssupporting
confidence: 62%
“…Besides significantly reducing testing time and thus enabling the evaluation of more testing conditions, the use of WSB structures provides data for the early failure mode, which defines the chip lifetime. Details describing this methodology were published previously [9,11]. The EM test matrices using WSB devices are shown in Fig.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Note that due to differences of scale, the x-axes vary between plots. The data appear to follow a bimodal distribution such as that seen by Hauschildt et al, 5 which disrupts the fit to the lognormal distribution shown in the plot and thereby increases the apparent standard deviation when plotted as a single mode lognormal. The assumption was made that either failure mode would react in the same way to any possible relaxation, so that separating the modes would not be necessary for this study.…”
Section: Datamentioning
confidence: 95%
“…It is therefore relevant to use directly the failure data of the whole chain. In the case of computing lifetime for a single link, failure data extracted directly from the whole chain should have been deconvoluted through conditional reliabilities (in order to include non-failed links) [10]. Stress conditions and sampling are resumed in Table 1.…”
Section: B Test Structure and Stress Conditionsmentioning
confidence: 99%